Prolonged contact with dendritic cells turns lymph node‐resident NK cells into anti‐tumor effectors. Issue 9 (12th July 2016) - Mingozzi, Francesca; Spreafico, Roberto; Gorletta, Tatiana; Cigni, Clara; Di Gioia, Marco; Caccia, Michele; Sironi, Laura; Collini, Maddalena; Soncini, Matias; Rusconi, Michela; von Andrian, Ulrich H; Chirico, Giuseppe; et al.
Abstract: Natural killer (NK) cells are critical players against tumors. The outcome of anti‐tumor vaccination protocols depends on the efficiency of NK‐cell activation, and efforts are constantly made to manipulate them for immunotherapeutic approaches. Thus, a better understanding of NK‐cell activation dynamics is needed. NK‐cell interactions with accessory cells and trafficking between secondary lymphoid organs and tumoral tissues remain poorly characterized. Here, we show that upon triggering innate immunity with lipopolysaccharide (LPS), NK cells are transiently activated, leave the lymph node, and infiltrate the tumor, delaying its growth. Interestingly, NK cells are not actively recruited at the draining lymph node early after LPS administration, but continue their regular homeostatic turnover. Therefore, NK cells resident in the lymph node at the time of LPS administration become activated and exert anti‐tumor functions. NK‐cell activation correlates with the establishment of prolonged interactions with dendritic cells (DCs) in lymph nodes, as observed by two‐photon microscopy. Close DC and NK‐cell contacts are essential for the localized delivery of DC‐derived IL‐18 to NK cells, a strict requirement in NK‐cell activation. Synopsis: Natural killer cells are innate immune cells that exert important anti‐tumor functions and can be exploited for immunotherapy. A better understanding of the dynamics of NK‐cell activation is essential to design NK cell‐mediated therapies. Long‐lasting interactions are established by dendritic cells (DCs) and NK cells in vivo in the presence of LPS. NK cells are not actively recruited at the draining lymph node early after LPS administration, but continue their regular homeostatic turnover. Only NK cells resident in the draining lymph node at the time of LPS administration are activated upon interaction with DCs. Anti‐tumor functions are exerted by the activated NK cells that leave the lymph node and reach the tumor. Abstract : Natural killer cells are innate immune cells that exert important anti‐tumor functions and can be exploited for immunotherapy. A better understanding of the dynamics of NK‐cell activation is essential to design NK cell‐mediated therapies.